Activity of the novel fungicide oxathiapiprolin against plant‐pathogenic oomycetes. Issue 8 (21st December 2015) - Miao, Jianqiang; Dong, Xue; Lin, Dong; Wang, Qiushi; Liu, Pengfei; Chen, Furu; Du, Yixin; Liu, Xili
Abstract: BACKGROUND: Oxathiapiprolin was the first of the piperidinyl thiazole isoxazoline class of fungicides to be discovered and developed by DuPont in 2007. Although oxathiapiprolin has been reported to have high activity against plant‐pathogenic oomycetes, such as Peronospora belbahrii, Phytophthora nicotianae and Ph. capsici, little is known about its effectiveness against other plant‐pathogenic oomycetes and its protective and curative properties. RESULTS: Oxathiapiprolin exhibited substantial inhibitory activity against all of the plant‐pathogenic oomycetes tested, with EC90 values ranging from 0.14 to 3.36 × 10 −3 µg mL −1, except the Pythium species Py. aphanidermatum and Py. deliense . Furthermore, doses as low as 10 µg mL −1 were found to inhibit zoospore release and motility in Ph. capsici, while the mycelial development and sporangial production of Pseudoperonospora cubensis were restrained by an EC50 of 3.10 × 10 −4 and 5.17 × 10 −4 µg mL −1 respectively. It was also found that oxathiapiprolin exhibited both protective and curative activity against the development of Ph. capsici infection in pepper plants under greenhouse conditions and in field tests. CONCLUSION: The present study demonstrated that the novel fungicide oxathiapiprolin exhibits strong inhibitory activity against a range of agriculturally important plant‐pathogenic oomycetes, including Phytophthora spp., Peronophythora litchii, Plasmopara viticola, Pe. parasitica, Ps. cubensis and Py. ultimum . © 2015 Society of Chemical Industry